Self-Esteem and Perseverance as Determinants of Self-Awareness among Higher Secondary School Students - Mr. Chhannu Lal Banjare; Dr. YashPal Singh (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research paper has been able to realize its 3 main objectives since it has analysed the correlations between the issues of self-esteem and perseverance and self-awareness among students in higher secondary schools with extensive statistical results to determine the results convincingly. The first goal was achieved when assessing the strength of the positive relationship between self-esteem and self-awareness (r = 0.67, p < 0.001), which proved that learners with high self-esteem possess much stronger introspection skills and metacognition acumen. The second aim was achieved by determining a strong positive correlation between perseverance and self-understanding (r = 0.58, p = 0.001), proving that those students who are more persistent and devoted to activities related to long-term objectives grow more self-aware through perseverance and override of challenges. Multiple regression analysis reached the third goal, showing that self-esteem and perseverance can predict self-awareness, and that they do so significantly (R 2 = 0.486, F (2, 397) = 187.64, p < 0.001) with self-esteem being the better predictor (x2 = 0.521) and the other contributing (x2 = 0.287) to the variance in the measure of self-awareness. The results of the study which are homogenous across different demographic aspects such as gender, geographical location, and academic stream serve as an empirical support to the fact that these two psychological constructs are intertwined and forms a basis of developing evidence-based educational programs which may not only improve self-esteem of adolescent learners but also will create well-being and enhance academic performance of learners.
Keywords: Self-esteem; Perseverance; Self-Awareness; Adolescent Development